Performance of zinc oxide and titanium dioxide nanoparticles on wood protection - Borges, Cilene Cristina (2019)
The use of wood presents several advantages over synthetic polymers, being wood the preferred material for many decorative and engineering applications. Some wood species, however, have little or lack of natural resistance to biological deterioration, and need protection. Through the time, several preservative treatments have been developed, but the search for new technologies with high efficiency, low environment toxicity, andno risks to human health still have been a challenge for researchers.The use of nanoparticles on wood protection is still incipient; however, nanotechnology has advanced considerably in recent years, opening the door for new experiments and knowledge applications, in the field of wood protection. The main objective of this work was to evaluate the performance of zinc oxide (ZnO) and titanium dioxide (TiO2) nanoparticles-based treatments on wood protection. Eucalyptus urophylla wood samples, made from ~7 years old trees, were vacuum-treated (45 min vacuum at 550 mmHg) with different concentrations of ZnO and TiO2 nanoparticles in water dispersion, i.e., a) 1 (2% ZnO); b) 2 (1.5% ZnO, 0.5% TiO2); c) 3 (1% ZnO; 1% TiO2); d) 4 (0.5% ZnO; 1.5% TiO2); e) 5 (2% TiO2); f) 6 (untreated). After treatments, wood samples were subject to accelerated fungal decay, termite bioassay and weathering. Chemical retentions were analyzed by inductively coupled plasma emission spectroscopy (ICP-AES), and penetration into wood were evaluated by scanning electron microscopy with energy dispersive spectroscopy - SEM/EDS analysis. The experiment was set in a completely randomized design.Results of chemical retention showed that ZnO retention decreased according to the decreasing of the oxide concentration of each treatment. TiO2 retentions of treatments were low detectable. Penetration of ZnO and TiO2 nanoparticles could be observed for each treatment performed. Mass loss of treated wood samples exposed to rot fungal decay in soil-block tests presented different results, according to the fungus and treatment performed. Termite bioassay performed with subterranean termite had chemical synergy on treatment 2. Besides, other two treatments, 1 and 3,considered statistically equivalents, showed average mass loss of 2.4and 3.1%, respectively, values considered as a low consumption.Average rating termite mortality were evaluated after four weeks, with three treatments rated at 100% of mortality: 1, 2, and3. Regarding weathering tests, treatment 5 presented brighter than all other treatmentsin the exposed face, while untreated ones were less bright and grayer than all treatments performed. In the unexposed face, treatment 1 was less gray and brighter than all treatments, including untreated samples. Based on the results, we can conclude that both zinc oxide and titanium dioxide show potential to perform an important role on the future of wood protection, and could be included as multi-components of a new generation of nanoparticles-based wood preservatives.